Dynamic strategy for sustainable business development: mania or hazard? - Jarmila Šebestová; Kateřina Nowáková (Amfiteatru Economic Journal, 2013)
The main goal of this paper is to present a practical model of sustainability ratio. In this context, the study provides an analysis of theoretical literature sources in area of strategy evaluation and possible measurement of success. The purpose of presented research was to discover the impact of external business environment factors (based on previous PESTLE analysis) on current strategic behavior in small and medium sized business area. The survey was conducted on SMEs in the Czech Republic in 2011 within own research project. The proposed model of sustainability ratio incorporates dynamic behavior and shows how manipulating certain items can alter outcomes in the strategic system in a predicable way. As a contribution to the literature, the paper highlights on the flexibility of business strategy types and which items are the most important for strategy making in an uncertain and turbulent environment.
Keywords: L26; M26; C12; 330; crisis behaviour; Czech firms; dynamic mania; dynamic effects; survival ratio; strategy